Hepatitis B and C virus and hepatocellular carcinoma (1997)
"Antibody to hepatitis C virus (anti-HCV) was detected in 18.7% of patients with hepatocellular carcinoma ma (HCC)a nd in 10.9% of controls (P<0.001).The corresponding prevalences of hepatitis B surface antigen [HBsAg] were 59.3% and 50.0%(P<0.001). Using paticnts with non-hepatic disease as controls stepwise logistics regression analysis indicated that both anti-HCV (odds ratio 6-88%; 9.5% confidence interval [CI] 1.63-9-77) and HBsAg (odds ratio 6.46; 95% Cl 1.68-18:13) were independent risk factors for HCC. Calculation of the incremental odds ratio indicated no interaction between hepatitis B virus {HBV) and HCV. Blood transfusion was a significant risk factor for acquiring HCV infection with odds ratios of 5.48 (95% CI 1.07-29.0) and 2.86 (95%. CI 1.31-22.72) for HCC cases and controls, respectively. The mean age HCC cases with HBsAg and anti-HCV was lower than that of HCC patients with anti-HCV alone (p<0.01). It is concluded that there is a high rate of HBV infection, and a low rate of HCV infection, among Nigerian patients with HCC. However, HBV and HCV are independent risk factors for the developement of HCC, with HBV having an effect more rapidly. Screening of blood products for transfusion might minimize the risk of HCV transmission."